MEMBINGKAI RELASI ORANG HIDUP DAN MATI MELALUI TRADISI LISAN UPACARA TEING HANG - Selatang, Fabianus (Studi Budaya Nusantara, 2020)
The teing hang, a traditional ceremony in honour to the ancestors or the deceased is deeply rooted within the culture of the Manggarai society. Although this ritual is part of the local culture it still has many unresolved issues. The questions that often arise are: is teing hang a religious syncretism? Is it a dualistic faith practice? Does this not contradict to the content and the essence of Christian faith? Is this a form of idolatry? These questions encourage writers to explore the depth of the significance and the message of the teing hang ceremony. This study aims to explore the relationship between the living and the dead based on the oral tradition of the teing hang ceremony. Conceptually, the idea of the relationship meant here is based on the concept of birth. In the frame of the birth concept, the Manggarai has built a pattern of relationship with the ancestors or deceased people. This research is carried out through the use of qualitative methods. The data is analysed through structural and semiotic studies. The data is taken from a traditional figure in village N Sub-district Macang Pacar, West Manggarai regency. The results of this study show that the practice of the teing hang ceremony in honour to the ancestors or deceased people is not a form of syncretism or idolatry. This is actually a way of proclaiming faith. The Church wants to say to the Manggarai society that by the teing hang ceremony there is a supranatual power that isn't enough explained by reason completely. The Church wishes to show to its believers that the message of the teing hang ceremony is far beyond what is visible to the human eyes. It is a spirituality rich ceremony that envelopes supernatural realities. Thus, the teing hang ceremony provides a new means of expressing faith through symbolic languages.